2012
DOI: 10.1177/0146167212439213
|View full text |Cite
|
Sign up to set email alerts
|

Low-Effort Thought Promotes Political Conservatism

Abstract: The authors test the hypothesis that low-effort thought promotes political conservatism. In Study 1, alcohol intoxication was measured among bar patrons; as blood alcohol level increased, so did political conservatism (controlling for sex, education, and political identification). In Study 2, participants under cognitive load reported more conservative attitudes than their no-load counterparts. In Study 3, time pressure increased participants' endorsement of conservative terms. In Study 4, participants conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 101 publications
(141 reference statements)
10
130
2
1
Order By: Relevance
“…And then this style of this attribution may take as a positive attributional style. On the other hand, if people attribute positive outcomes to effort, the positive affective reaction is too feeble to strength the behavior reaction which may be considered as negative attributional styles (Shepperd et al Eidelman et al 2012). However, this may not true in Chinese culture and the above inferences were not proved in the CFA results of current study which showed the important need for contextualized research of the structure of attributional style.…”
Section: Discussionmentioning
confidence: 99%
“…And then this style of this attribution may take as a positive attributional style. On the other hand, if people attribute positive outcomes to effort, the positive affective reaction is too feeble to strength the behavior reaction which may be considered as negative attributional styles (Shepperd et al Eidelman et al 2012). However, this may not true in Chinese culture and the above inferences were not proved in the CFA results of current study which showed the important need for contextualized research of the structure of attributional style.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research on personality characteristics documents a link between conservative political orientation (especially when it comes to social and cultural issues) and lower openness to new experiences and higher conscientiousness (e.g., Carney et al, 2008). In line with these findings, conservatism is also associated with epistemic needs to maintain certainty, structure, and closure, along with a generally rigid or persistent cognitive style (Eidelman, Crandall, Goodman, & Blanchar, 2012;Jost et al, 2003Jost et al, , 2008Jost et al, , 2009Jost & Krochik, 2014;Thorisdottir & Jost, 2011;Tetlock, 1983). …”
Section: Psychological Underpinnings Of Political Orientationmentioning
confidence: 90%
“…The immediate response to this threat involves prevention (vs. promotion) reactions that emphasize what is already known and familiar (i.e., the status quo), in the interest of reducing uncertainty and anxiety and minimizing potential harm or danger. As such, prevention responses and "conservative" reactions are both basic and normal (Eidelman et al, 2012), triggered by an oversensitivity to the unfamiliar (or to perceived threats) but also representing a reasonable response based on a critical evaluation of threatening environmental factors.…”
Section: An Integrative Model Of Cognitive Ability and Style To Evalumentioning
confidence: 99%
“…Furthermore, Eidelman, Crandall, Goodman, and Blanchar (2012) have provided experimental support that low-effort thinking promotes political conservatism. Linear relations have also been confirmed longitudinally, with poorer mental abilities in childhood predicting stronger endorsement of right-wing authoritarianism and social conservatism (e.g., Deary et al, 2008a;Heaven et al, 2011;Hodson & Busseri, 2012;Schoon et al, 2010) and right-leaning voting behavior (Deary, Batty, & Gale, 2008b) in adulthood.…”
mentioning
confidence: 98%